2017
DOI: 10.1017/s0007114517000253
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk fatty acid composition and fatty acid intake of lactating mothers in South Korea

Abstract: The aim of this study was to determine the fatty acid (FA) composition of breast milk, and its association with mothers' FA intake. Milk samples were obtained from 238 healthy lactating women who volunteered to participate in the Human Milk Micronutrients Analysis Research. Dietary intake during lactation was assessed using a 3-d food record, and fat content and FA composition of the breast milk samples were analysed by IR spectrometry using MilkoScan FT2 and GC flame ionisation detector, respectively. The fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
7
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 42 publications
6
119
7
8
Order By: Relevance
“…The MUFA in our study was comparable to Asian data (10,(21)(22)(23)(24)(25) but was much lower than Mediterranean studies (7,27) , mainly due to the lower level of OA (online Supplementary Table S1).…”
Section: Mufasupporting
confidence: 79%
See 1 more Smart Citation
“…The MUFA in our study was comparable to Asian data (10,(21)(22)(23)(24)(25) but was much lower than Mediterranean studies (7,27) , mainly due to the lower level of OA (online Supplementary Table S1).…”
Section: Mufasupporting
confidence: 79%
“…SFA (37•18-41•63 %) dominated in fatty acid profile over the three lactation stages. The SFA content in mature stage was reported as slightly higher than other studies conducted in China (10,(21)(22)(23) and slightly lower than conducted in Japan (24) , South Korean (25) and some European countries (24) (online Supplementary Table S1). Dietary pattern was commonly considered the major contributor.…”
Section: Sfacontrasting
confidence: 58%
“…It has been reported that fatty acid concentrations in human milk are reflective of maternal food intake. 11 The values we report are higher concentrations than those reported in the literature.…”
Section: Discussioncontrasting
confidence: 64%
“…Chinese human milk studies (5,28,29) including our present one all reported a typically higher percentage of PUFA (22•40-30•04 %) than those (17•25-21•50 %) in the developed Asian countries (30,31) and those (14•68-19•71 %) in the Western countries (32)(33)(34) , which was mainly due to the higher levels of human milk LA (18•90-25•10 %) in China (5,28,29) than in developed countries (11•48-16•59 %) (30)(31)(32)(33)(34) . Consequently, a fairly high ratio of LA: ALA (16:1) was observed in the mature milk of our study, which was on the top of the range of (9•26-16•50):1 in the latest reports from China (5,28,29) .…”
Section: Fatty Acidsmentioning
confidence: 52%